ریاست کا تعلیمی نظام سیرت النبی ﷺکی روشنی میں: Education system of a state in the light of Serah (PPBUH) - Dr. Noor Hayat (Seerat Studies, 2023)
This study examines the educational framework of the Islamic state as envisioned in the life and teachings of the Prophet Muhammad (PBUH). It explores the integral role of education in fostering both individual and societal development within a welfare- oriented Islamic state. The paper defines the components of a state, emphasizing the importance of political order, constitutional adherence, and territorial sovereignty, while aligning these with the principles of Islamic teachings. Highlighting the transformative educational methodologies employed during the Prophet’s time. The study discusses the significance of integrating spiritual, moral, and intellectual education to establish a cohesive and progressive society. It also critiques modern secular educational systems for their detachment from religious and ethical values, advocating for a holistic educational model inspired by Seerah. By linking education to governance, social harmony, and the broader objectives of Sharia, this research underscores the necessity of cultivating knowledge systems rooted in Islamic values to ensure societal stability and moral accountability. Key words: Education, state, methodology, development, sociate, Serah.